Diseño de mobiliario para el uso inclusivo de instalaciones deportivas públicas de Bogotá (2022)
This document presents the undergraduate work process to obtain the title of designer industry from the Antonio Nariño University. The project proposed to design furniture to help athletes in wheelchairs make fair use of the preparation spaces in public sports facilities in Bogotá. The problem started of the evident lack of adequate equipment in the facilities provided for these practices, which goes against the inclusive character that they should have, because in the city ​​this population has not been fully contemplated in the design, construction and endowment of infrastructures of great importance in the reconstruction of the social fabric and more appropriate integration of populations traditionally excluded from urban life